2009
DOI: 10.3324/haematol.2009.013458
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplantation for autoimmune diseases: an observational study on 12 years' experience from the European Group for Blood and Marrow Transplantation Working Party on Autoimmune Diseases

Abstract: BackgroundAutologous hematopoietic stem cell transplantation has been used since 1996 for the treatment of severe autoimmune diseases refractory to approved therapies. We evaluated the long-term outcomes of these transplants and aimed to identify potential prognostic factors. Design and MethodsIn this observational study we analyzed all first autologous hematopoietic stem cell transplants for autoimmune diseases reported to the European Group for Blood and Marrow Transplantation (EBMT) registry between 1996-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
272
1
29

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(312 citation statements)
references
References 46 publications
10
272
1
29
Order By: Relevance
“…Approximately 45 % of patients have a stable EDSS score at 5 to 7 years after HSCT [21,51,54]. Although the accumulated outcome data of HSCT for MS is largely from cohort studies that lack a randomized control group, most of the patients selected for HSCT had ongoing progression and had previously exhausted all other therapeutic options.…”
Section: Lesson 6: Hsct Can Results In Long-term Progression-free Outcmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 45 % of patients have a stable EDSS score at 5 to 7 years after HSCT [21,51,54]. Although the accumulated outcome data of HSCT for MS is largely from cohort studies that lack a randomized control group, most of the patients selected for HSCT had ongoing progression and had previously exhausted all other therapeutic options.…”
Section: Lesson 6: Hsct Can Results In Long-term Progression-free Outcmentioning
confidence: 99%
“…There is a large worldwide experience using autologous HSCT for MS [9,21], however, only a few transplants have been performed using human leukocyte antigen (HLA) matched allogeneic or donorderived HSC grafts. More than 95 % of recipients of autologous HSC have received grafts collected by peripheral vein leukopheresis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There was a reduction in the incidence of SAEs during the course of the trial (data not shown) implying that centres became more proficient at managing HSCT with experience. 29 It is relevant to note that patients in both groups received 4g/m 2 cyclophosphamide at mobilisation.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous transplant-related mortality is approximately 3-5% for patients with myeloma and lymphoma and approximately 5-10% for those with scleroderma (23, 27, 30, 31). Transplant is an intensive procedure with significant side effects including nausea, vomiting, diarrhea and oral mucositis which usually resolve with blood count recovery.…”
Section: The Process Of Autologous Hsctmentioning
confidence: 99%